Erythema and Acclimatization Following Repeated Sun Exposure: A Modeling Study. (27th June 2021) - Diffey, Brian
Abstract: The development of a computational model is described that allows time‐varying erythema and acclimatization to be determined following repeated exposure to solar ultraviolet (UV) radiation. Good agreement was observed between experimental data and model predictions. Results are presented that illustrate how daily, adventitious sun exposure over the course of a year can result in occasional erythema generally in the late spring/early summer, while at the same time showing how the photoadaptive response of the skin changes throughout the year at different latitudes and for different sun‐reactive skin types. The model is predicated on three physiological responses; the erythemal response as a function of increasing UV dose, the time courses of erythema and adaptation in response to a single UV exposure. Mathematical models complement observational data and the outputs from the model may help in planning future experimental studies, as well as providing insights into mechanistic responses. Abstract : A computational model that allows time‐varying erythema and acclimatization to be determined following repeated UV exposure has been developed. This plot illustrates how daily casual sun exposure over the course of a year can result in occasional mild erythema (red curve) in the late spring/early summer while at the same time showing how the photoadaptive response of the skin (black curve) changes throughout the year.